Antinuclear Matrix Protein 2 Autoantibodies and Edema, Muscle Disease, and Malignancy Risk in Dermatomyositis Patients - Albayda, Jemima; Pinal‐Fernandez, Iago; Huang, Wilson; Parks, Cassie; Paik, Julie; Casciola‐Rosen, Livia; Danoff, Sonye K.; Johnson, Cheilonda; Christopher‐Stine, Lisa; Mammen, Andrew L. (Arthritis care & research (2010), 2017)
Objective Dermatomyositis (DM) patients typically present with proximal weakness and autoantibodies that are associated with distinct clinical phenotypes. We observed that DM patients with autoantibodies recognizing the nuclear matrix protein NXP‐2 often presented with especially severe weakness. The aim of this study was to characterize the clinical features associated with anti–NXP‐2 autoantibodies. Methods There were 235 DM patients who underwent testing for anti–NXP‐2 autoantibodies. Patient characteristics, including muscle strength, were compared between those with and without these autoantibodies. The number of cancer cases observed in anti–NXP‐2‐positive subjects was compared with the number expected in the general population. Results Of the DM patients, 56 (23.8%) were anti–NXP‐2‐positive. There was no significant difference in the prevalence of proximal extremity weakness in patients with and without anti–NXP‐2. In contrast, anti–NXP‐2‐positive patients had more prevalent weakness in the distal arms (35% versus 20%; P = 0.02), distal legs (25% versus 8%; P < 0.001), and neck (48% versus 23%; P < 0.001). Anti–NXP‐2‐positive subjects were also more likely to have dysphagia (62% versus 35%; P < 0.001), myalgia (46% versus 25%; P = 0.002), calcinosis (30% versus 17%; P = 0.02), and subcutaneous edema (36% versus 19%; P = 0.01) than anti–NXP‐2‐negative patients. Five anti–NXP‐2‐positive subjects (9%) had cancer‐associated myositis, representing a 3.68‐fold increased risk (95% confidence interval 1.2–8.6) compared to the expected prevalence in the general population. Conclusion In DM, anti–NXP‐2 autoantibodies are associated with subcutaneous edema, calcinosis, and a muscle phenotype characterized by myalgia, proximal and distal weakness, and dysphagia. As anti–NXP‐2‐positive patients have an increased risk of cancer, we suggest that they undergo comprehensive cancer screening.